THE SEARCH FOR MUSLIM UNITY AND PARTICULARITIES OF ITS REFLECTION IN THE LITERATURE - I. A. KAZHAROVA (Кавказология, 2021)
The article examines the aspects of the involvement of the Adygs in the internal relations of the Islamic world, assesses the inevitability of their contact with the ideas of Islamic reformism and the reflection of these ideas in the literature. The relevance of the study is due to the fact that the reflection of the paradigm of Islamic reformism in the written culture of the Adygs is one of the least studied pages of it. The few artistic reflections that are discussed in the work capture a clear attitude to the Turkophile tendencies that have emerged in the mainstream of this paradigm. In the didactic and journalistic writings of the leaders of the Baksan cultural movement, one can see the authoritative affiliation of the ideas they develop. However, it is not so much the socio-political aspects of the idea of Muslim unity that dominate, but its cultural potential, which opens up the possibility of reviving its own ethnic world.